The Influence of Additional Feeding (Sproads) on the Microscopic Quality of Spermatozoa of Bali Caws in BIBD Banyumulek, West Nusa Tenggara Province - Imam Munandar (Animal Science Study Program, Faculty of Agriculture, Science and Health, Universitas Timor, 2026)
This study aims to determine the effect of supplementary feeding of bean sprouts on the microscopic quality of Balinese cattle spermatozoa at the Regional Artificial Insemination Center of West Nusa Tenggara Province. Microscopic semen evaluation includes volume, mass movement, individual movement, motility and concentration. The design used was a complete randomized design (CRD) and data analysis using Anova which was further tested using Duncan. The mass movement of Balinese spermatozoa in P1 and P2 has a percentage value of 67% (+++), which indicates that the spermatozoa move to form large and progressive waves. Individual motion in P2 produces a very progressive motion with the highest percentage of 60%. The results of the analysis of volume, motility and concentration of Balinese spermatozoa showed significantly different results in P2, namely the treatment with the addition of 4 kg of bean sprouts. Based on the results of this study, it shows that there is an effect of supplementary feeding of bean sprouts with the treatment of 4 kg per week on the microscopic quality of Balinese spermatozoa at the Regional Artificial Insemination Center of NTB Province.